2007
DOI: 10.1021/jo070161m
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Retro-cycloaddition Reaction of Isoxazolino[4,5:1,2][60]- and -[70]fullerenes

Abstract: Isoxazolino[4,5:1,2][60]- and -[70]fullerenes undergo an efficient retro-cycloaddition reaction to pristine fullerene by thermal treatment in the presence of an excess of a dienophile and Cu(II) catalysis, which can be selectively used in the presence of malonate or pyrrolidine cycloadducts. Trapping experiments using N-phenylmaleimide as dipolarophile have shown that the reaction mechanism occurs by thermal removal of the nitrile oxide 1,3-dipole, in a process which is favored by the presence of Cu(II) as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…In this case, with comparable intensity to [C 60 ] + , a fragment at m/z 752 corresponding to [C 60 S] + was also found [41]. Similar results are found in the ESI-MS/MS spectra in positive mode from fullerene fused to heterocyclic rings containing oxygen atoms such as isoxazolinofullerenes (also two heteroatoms in the heterocyclic moiety), which fragment leading to a fragment [C 60 O+H] + [25]. In contrast, an analogous fragment [C 60 NH+H] + is not observed in the MS/MS mass spectra of nitrogen containing heterocyclic fullerenes.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In this case, with comparable intensity to [C 60 ] + , a fragment at m/z 752 corresponding to [C 60 S] + was also found [41]. Similar results are found in the ESI-MS/MS spectra in positive mode from fullerene fused to heterocyclic rings containing oxygen atoms such as isoxazolinofullerenes (also two heteroatoms in the heterocyclic moiety), which fragment leading to a fragment [C 60 O+H] + [25]. In contrast, an analogous fragment [C 60 NH+H] + is not observed in the MS/MS mass spectra of nitrogen containing heterocyclic fullerenes.…”
Section: Resultssupporting
confidence: 80%
“…Because C 60 acts as an electron poor olefin, the cycloaddition reaction with azomethine ylides leads to the formation of pyrrolidinofullerenes [22,23] while the dipolar cycloaddition of nitrile imines affords the corresponding pyrazolinofullerenes [24]. During the course of our investigations on the homo-and heterocyclic fullerene cycloadducts, we have observed that the molecular odd-electron ions generated under ESI conditions and negative mode of detection from substituted isoxazolinofullerenes [25] . On the other hand, the retro-Diels-Alder reaction (RDA) is a wellknown process, which can be generated in a mass spectrometer [26][27][28], and is one of the most investigated spectrometric process in the fullerene chemistry [29][30][31].…”
Section: Introductionmentioning
confidence: 91%
“…[13][14][15] C 60 reacts with different nitrile oxides forming [6,6]fullerene-isoxazolines, where in this case the retro-cycloaddition was also possible. [16][17][18] There are no experimental results for the addition of simple nitrones to fullerenes as they are very unstable; however, the addition of N-silyloxynitrones to C 60 has been investigated. [19] The 1,3-dipolar cycloadditions of diazomethane, nitrile oxide, and nitrone to C 60 were studied Keywords: cycloaddition · density functional calculations · Diels-Alder reactions · distortion/interaction theory · Marcus theory · ONIOM Abstract: Diels-Alder cycloadditions of butadiene and 1,3-dipolar cycloadditions of azomethine ylide, fulminic acid, and the parent nitrone to polyacenes, fullerenes, and nanotubes have been investigated with density functional theory and ONIOM methods.…”
Section: Introductionmentioning
confidence: 99%
“…[15] To investigate the potential of isoxazolines to serve as a protective group in the synthesis of fullerene pentakisadducts, we targeted the synthesis of mixed [5:1]hexakisadduct 1 c (Scheme 1), which bears ten acid-labile tert-butyl-protected carboxylic groups. Fivefold cyclopropanation with bis[3-(tert-butoxycarbonyl)propyl] malonate [18] was achieved by using the modified reaction conditions for the synthesis of fullerene hexakisadducts [19,20] in 42 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…[13,14] More recently, it was reported that isoxazolines can also be cleaved under less harsh conditions by heating to reflux in o-dichlorobenzene with an excess amount of a dienophile and Cu II catalysis. [15] We report now a much milder photolytic cleavage of a mixed [5:1]-fullereno isoxazoline adduct 1 prepared from the isoxazolinofullerene 2 [15][16][17] to yield directly C 2v -symmetrical pentakisadducts. The discovery opens now the door to very facile access to complex fullerene-based architectures that involve a mixed octahedral addition pattern.…”
Section: Introductionmentioning
confidence: 93%